Infringement and Protection of Copyrights in the Age of Internet - SUMANJEET, Singh; MINAKSHI, Paliwal (Journal of Advanced Research in Law and Economics; Vol 4 No 2 (2013): JARLE Volume IV Issue 2(8) Winter 2013, 2016)
The interaction between copyright and technology represents one of the greatest challenges for regulators because the latter is constantly evolving, the former needs to adapt to the latter’s constant evolution. In this light, the present paper draws attention to the problem of copyright infringement in the age of the internet. The paper also discusses the issues relating to protection of copyright infringement. In the end, the paper seeks to outline a general framework for addressing the problem of copyright infringement on the internet. The paper concludes that only technical and legal measures will not be able to completely stop the illegitimate distribution of pirated content. The paper suggests that a comprehensive solution is needed to manage the problems associated with internet copyright infringement, including increased law enforcement, upgraded technological measures, innovative business strategy and educational awareness about copyright issues.
Keywords: copyright, infringement, Internet, piracy